Amelioration of Cigarette Smoke-Induced Hepatic Injury by Green Tea (Camellia sinensis) Extract: Evidence from SGOT and SGPT Biomarkers in a Murine Model - Indrajaya, Putra; Mudawamah, Mudawamah; Kalsum, Umi; Trisakti, Adinda Rizky; Rahmatullah, Aldin Akbar (Journal of Basic Medical Veterinary, 2025)
This study investigated the hepatoprotective effects of green tea extract (GTE) against cigarette smoke-induced liver damage in mice. Twenty-five male mice (Mus musculus) were divided into five groups: negative control (C-), positive control exposed to cigarette smoke (C+), and three experimental groups exposed to cigarette smoke and treated with different doses of GTE: 20 mg/kg BW (T1), 40 mg/kg BW (T2), and 60 mg/kg BW (T3). Following 36 days of treatment, serum SGOT and SGPT levels were measured as biomarkers of hepatocellular injury. Results showed significant elevation of both enzymes in the C+ group (SGOT: 50.46 ± 2.49 U/L; SGPT: 19.48 ± 1.47 U/L) compared to the C- group (SGOT: 35.10 ± 2.49 U/L; SGPT: 10.22 ± 1.68 U/L), indicating cigarette smoke-induced hepatotoxicity. GTE administration demonstrated dose-dependent hepatoprotection, with the highest dose (T3) showing the most substantial effect (SGOT: 38.26 ± 1.25 U/L; SGPT: 11.01 ± 1.05 U/L). Statistical analysis revealed significant differences between groups (p<0.05). The hepatoprotective mechanisms of GTE likely involve its potent antioxidant properties, enhancement of endogenous antioxidant systems, anti-inflammatory effects, modulation of xenobiotic metabolism, and mitochondrial protection. These findings suggest that green tea extract may serve as a promising natural hepatoprotective agent against cigarette smoke-induced liver injury, with potential applications in preventive healthcare strategies.